(NsEJSMOAKUSTI^ESKIE ISSLEDOWANIQ mIROWOGO OKEANA (B:s (NsBORNIK NAU^NYH TRUDOW (B/s - (NbQKOW(B, (N`(B.(Na(B.s; (NgRA[KIN(B, (Ng(B.(Nn(B.s; (NgLUMOW(B, (Ni(B.(Nf(B.s ((NgELENDVIK (B:s (Npo `VMORGEOLOGIQ(B,s, 1986)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(NnAU^NO(B-(NISSLEDOWATELXSKIJ I PROEKTNYJ IN(B-(NT GEOFIZI^ESKIH METODOW RAZWEDKI OKEANAs
Keywords: (NoKEANYs; (NsEJSMOAKUSTI^ESKIE ISSLEDOWANIQs